2013
DOI: 10.1007/s12028-012-9813-y
|View full text |Cite
|
Sign up to set email alerts
|

Troponin Elevation in Subarachnoid Hemorrhage Does not Impact In-hospital Mortality

Abstract: Troponin I elevation after SAH is not an independent predictor of in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…This observation concurs with some of the previous studies [1, 11]. Meanwhile, studies reporting elevated troponin as a prognostic risk factor for mortality were not adjusted for other cardiovascular abnormalities [10, 20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation concurs with some of the previous studies [1, 11]. Meanwhile, studies reporting elevated troponin as a prognostic risk factor for mortality were not adjusted for other cardiovascular abnormalities [10, 20].…”
Section: Discussionsupporting
confidence: 91%
“…Sub-arachnoid hemorrhage (SAH) is associated with a high mortality, particularly within the first 48 h of presentation [1, 2]. Although cardiac injury in SAH has been previously described [35], the prognostic implications of cardiac injury and its relationship with short-term mortality remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…After title screening and detailed abstract evaluation, 46 studies were selected. After detailed evaluation of the full 46 article, 12 studies [8][9][10][11][12]18,[24][25][26][27][28][29] were selected for inclusion in this review. No overlap was found among these 12 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…It was measured repeatedly for consecutive days, [8][9][10][11][12]27 on the day of admission only, 18,24,26,28 or both. 25,29 …”
Section: Study Characteristicsmentioning
confidence: 99%
“…Several complications such as intraventricular hemorrhage (IVH), acute hydrocephalus, early hematoma expansion, and perihemorrhagic edema may occur during hospital stay and have been previously verified to independently impact outcome [2][3][4][5][6]. In addition, recent studies reported a high rate of cardiac complications presumably linked to a further increase in mortality of patients with intracranial hemorrhage [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%